2021
DOI: 10.1088/1361-6471/ac2679
|View full text |Cite
|
Sign up to set email alerts
|

Flux tubes in full QCD at high temperature

Abstract: Chromoelectric and chromomagnetic field and energy density distributions produced by a quark-antiquark pair have been investigated in the presence of dynamical fermions in the close vicinity to the deconfinement phase transition. In our lattice simulation we have used highly improved staggered quark action and tree level improved Symanzik gauge (HISQ/tree) action on the lattices of two different sizes, exploiting the Gradient flow method for noise reduction. We find that, in full QCD with dynamical quarks, the… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 27 publications
0
1
0
Order By: Relevance
“…A review of the confinement problem in QCD can be found in [1]. A large number of numerical studies provide evidence of confinement both in pure gauge SU (2) and SU(3) theories , and, more recently, in full QCD [30][31][32][33]. From these studies, we know that at temperatures below the deconfinement temperature T dec , the interaction between a static quark and antiquark is governed by a linear potential, that is observed for quark-antiquark separation d ≥ 0.5 fm.…”
Section: Introductionmentioning
confidence: 99%
“…A review of the confinement problem in QCD can be found in [1]. A large number of numerical studies provide evidence of confinement both in pure gauge SU (2) and SU(3) theories , and, more recently, in full QCD [30][31][32][33]. From these studies, we know that at temperatures below the deconfinement temperature T dec , the interaction between a static quark and antiquark is governed by a linear potential, that is observed for quark-antiquark separation d ≥ 0.5 fm.…”
Section: Introductionmentioning
confidence: 99%